Ozone-assisted combustion and emission control in RCCI engines: A comprehensive study - Firat, Mujdat; Senocak, Safak Melih; Okcu, Mutlu; Varol, Yasin; Altun, Sehmus (Pergamon-Elsevier Science Ltd, 2023)
This paper presents an investigation into the combustion and emission characteristics of reactivity-controlled compression ignition (RCCI) engines using ozone seeding, which is known as one of the most highly oxidizing chemical species. The study aims to address challenges pertaining to combustion control and emissions deterioration. Therefore, the current work investigates the RCCI mode of operation in a single-cylinder diesel engine with intake air that has been seeded with ozone by introducing conventional diesel fuel as a high-reactivity fuel using a high-pressure direct injection method and iso-octane as a low reactivity fuel using a low-pressure port injection method. In the experimental study, different ozone concentrations up to 300 ppm and three different energy-based premixed ratios of low reactivity fuel from 0% to 45% with a 15% rise rate were examined under various engine loads and constant engine speed. The methodology used in this research provided for simultaneous decreases in unburned hydrocarbon (HC) emissions and smoke opacity for RCCI engines. According to the experimental findings, simultaneous utilization of RCCI mode and ozone seeding led to a decrease of up to 36% in HC emissions and a reduction of up to 98.7% in smoke opacity. Moreover, nitrogen oxides (NOx) emissions were reduced by up to 39.5% at 20% engine load, whereas carbon monoxide (CO) emissions exhibited a decrease of up to 46% at 60% load. The RCCI mode also yields significant reductions in pollutant emissions and notable increases in brake thermal efficiency (BTE) when compared to the conventional diesel mode (CDM). In conclusion, this experimental study presents a promising solution for addressing emissions deterioration in RCCI engines while simultaneously achieving reductions in pollutant emissions.
Keywords: Reactivity controlled compression ignition; Ozone (O 3 ); Combustion; Diesel engines; Emissions